Working Together: Cooperation or Collaboration? - Kvellestad, Randi Veiteberg; Stana, Ingeborg; Vatn, Gunhild (FormAkademisk, 2021)
Teamwork involves different types of interactions—specifically cooperation and collaboration—that are necessary in education and many other professions. The differences between cooperation and collaboration underline the teacher’s role in influencing group dynamics, which represent both a foundation for professional design education and a prequalification for students’ competences as teachers and for critical evaluation. As a test case, we focused on the Working Together action-research project in design education for specialised teacher training in design, arts, and crafts at the Oslo Metropolitan University, which included three student groups in the material areas of drawing, ceramics, and textiles. The project developed the participants’ patience, manual skills, creativity, and abilities, which are important personal qualities for design education and innovation and represent cornerstones in almost every design literacy and business environment. The hope is that students will transform these competences to teaching pupils of all ages in their future careers.